EVALUATION OF MAXILLO - FACIAL TRAUMA BY USING MULTI-DETECTOR COMPUTED TOMOGRAPHY IN TAIF CITY, KINGDOM OF SAUDI ARABIA - Elrashed Abd Elrahim1 , Osama Awadh Najem AL-Otaibi2 , Abdullah Saad Aljauid3 , Mohammed Ahmed Alsharif4 , Rehab Hameed AL-Otaibi4; Mohammed Mosleh SalmanAlghoraibi5 (Chelonian Research Foundation, 2023)
Frequent Trauma to the facial region may lead to severe complications such as sinuses obstruction, intracranial injuries, sensory disturbance, and loss of vision. Multi-detector Computed Tomography (MDCT) has a critical and significant rule for early evaluation of the facial region. This study aimed to evaluate the findings that occur due to facial injuries using MDCT. Analytical retrospective study of 100 patients with facial bone injuries examined by CT scan. The study extended from January 2022 to January 2023. 128 slice CT systems (Siemens Medical system) was applied to investigate patients with facial trauma at King Abdul-Aziz Specialist Hospital (KAASH) in Taif city, KSA. a total of 100 facial trauma (87%) males and 13(13%) females, were examined via facial CT and presented with various types of trauma. The findings have noticed that the maxillofacial fractures were significantly higher in the male population (87%) than the female population (13%) Based on age groups. The incidence percentage of facial fractures was 50%, happened in the age group 20-39 years. The most common cause of injury in patients presenting with facial trauma was road traffic accidents, comprising 41% of cases. The most frequent fracture was nasal bone 75%.the majority facial fractures were recognized during a facial CT scan, and the majority of the patients were male. The Nasal bone was the most common site of the fracture, followed by Orbital bones. Therefore, CT is essential for the patient with facial trauma for early management to avoid any further complications for the patient. Keywords: Maxillofacial, CT, MDCT, Injuries, multi-detector, Fractures